2023
DOI: 10.1002/elsc.202300070
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and childhood malnutrition: Understanding the link and exploring therapeutic interventions

Sevda Zoghi,
Fatemah Sadeghpour Heravi,
Zeinab Nikniaz
et al.

Abstract: Childhood malnutrition is a metabolic condition that affects the physical and mental well‐being of children and leads to resultant disorders in maturity. The development of childhood malnutrition is influenced by a number of physiological and environmental factors including metabolic stress, infections, diet, genetic variables, and gut microbiota. The imbalanced gut microbiota is one of the main environmental risk factors that significantly influence host physiology and childhood malnutrition progression. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 182 publications
(213 reference statements)
0
2
0
Order By: Relevance
“…Tang et al delves into the intricate interplay between the gut microbiota and the host epigenome in the context of Non-alcoholic Fatty Liver Disease (NAFLD), shedding light on how microbial factors can modulate gene expression patterns associated with NAFLD pathogenesis [1]. Similarly, Zoghi et al investigate the association between gut dysbiosis and nutritional imbalances in children, underscoring the potential therapeutic avenues for modulating gut microbiota composition to restore energy homeostasis [2].…”
Section: Microbiome Research For Advancing Engineering In Life Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al delves into the intricate interplay between the gut microbiota and the host epigenome in the context of Non-alcoholic Fatty Liver Disease (NAFLD), shedding light on how microbial factors can modulate gene expression patterns associated with NAFLD pathogenesis [1]. Similarly, Zoghi et al investigate the association between gut dysbiosis and nutritional imbalances in children, underscoring the potential therapeutic avenues for modulating gut microbiota composition to restore energy homeostasis [2].…”
Section: Microbiome Research For Advancing Engineering In Life Sciencementioning
confidence: 99%
“…Similarly, Zoghi et al. investigate the association between gut dysbiosis and nutritional imbalances in children, underscoring the potential therapeutic avenues for modulating gut microbiota composition to restore energy homeostasis [ 2 ].…”
mentioning
confidence: 99%
“…Emerging research suggests that certain herbs may positively influence gut microbiota composition, potentially leading to improved health outcomes. 38 Studies have shown that certain herbs, such as turmeric, flaxseed, and chicory root, exhibit prebiotic properties, which are non-digestible fibers that serve as food for beneficial gut bacteria. Prebiotics promote the growth and activity of bacteria, such as Bifidobacteria and Lactobacillus, known for their positive effects on gut health and immune function.…”
Section: Potential Impact Of Herbal-based Nutraceuticals On Gut Micro...mentioning
confidence: 99%